Fact-Checking Journalism sebagai Platform Kolaborasi Human and Machine pada Jurnalisme Digital - Mufti Nurlatifah; Irwansyah Irwansyah (Program Studi Ilmu Komunikasi, 2019)
Fact-checking journalism becomes a new trend in journalism studies. The peculiarities of fact-checking journalism are the collaborations which developed beyond boundaries of the editorial room and conventions of journalism. Human and machine disruptions within fact-checking journalism are unavoidably developed into hypermedia organization. Collaboration is built amongst journalist, user, and digital media application in order to describe the whole factual context This paper reviews this phenomenon as main concept of hypermedia organization manifestation in fact-checking journalism. Keywords: digital journalism, fact-checking, hypermedia organization, collaboration